Kualitas dan Masa Simpan Brownies Satin Berbasis Tepung Mocaf danTepung Ikan Patin - Kodriah, Nur Rahmawati; Hastuti, Widi (JGK: Jurnal Gizi dan Kesehatan, 2021)
Background : Anemia is one of the main problems experienced by many young women. The prevalence of anemia in adolescent girls (15-24 years) in 2018 is 32%. Efforts that can be made are by increasing the intake of iron sources especially animal food sources. Brownies become a distraction that is widely favored by the wider community. Utilization of mocaf flour and catfish flour as the main ingredient in the manufacture of brownie products will increase the nutritional value especially the iron content of the product. The purpose : of this study was to determine the quality and shelf life of satin brownies as a high-fer snack for young girls. Methods : Design of experimental research based on mocaf flour and catfish flour. A hedonic test was carried out by 30 panelists at the Nutrition Test Laboratory for the Department of Nutrition of the Poltekkes Ministry of Health, Bandung and the estimated shelf life using the Extend Storage Studies (ESS) method. The results : Organoleptic test results showed the highest level of panelist preference was at F2. Based on statistical tests found that there is an effect of the formulation on the aroma of F1 and F3 with a value of p = 0.015 and texture of F1 and F3 with a value of p = 0.016. The results of the calculation of the nutritional value of satin brownies compared with 10% of the AKG of female teenage snacks obtained 101% energy, 113% protein, 140% fat, 72% carbohydrate and 149% Fe. Shelf life of satin brownies at room temperature for 3 days. Suggestion : Based on the results of research it is necessary to do further research in the laboratory regarding the iron content contained in satin brownies